2020
DOI: 10.1038/s41392-020-0171-5
|View full text |Cite
|
Sign up to set email alerts
|

ALDH2 contributes to melatonin-induced protection against APP/PS1 mutation-prompted cardiac anomalies through cGAS-STING-TBK1-mediated regulation of mitophagy

Abstract: Ample clinical evidence suggests a high incidence of cardiovascular events in Alzheimer’s disease (AD), although neither precise etiology nor effective treatment is available. This study was designed to evaluate cardiac function in AD patients and APP/PS1 mutant mice, along with circulating levels of melatonin, mitochondrial aldehyde dehydrogenase (ALDH2) and autophagy. AD patients and APP/PS1 mice displayed cognitive and myocardial deficits, low levels of circulating melatonin, ALDH2 activity, and autophagy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 68 publications
1
45
0
Order By: Relevance
“…In this regard, MLT should be superior to other adjuvants in terms of safety, cost-effectiveness, and efficacy for large-scale cellular materials undergoing long-term expansion, although the comprehensive mechanisms are still under investigation. In regard to the therapeutic function of MLT, in vivo MLT application restored autophagic flux to impede cognitive decline and cardiac anomalies in Alzheimer’s disease (AD) animal models [ 27 , 28 ]. More recently, MLT was demonstrated to downregulate PI3K/AKT in stem cells through the MLT receptor (MT) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, MLT should be superior to other adjuvants in terms of safety, cost-effectiveness, and efficacy for large-scale cellular materials undergoing long-term expansion, although the comprehensive mechanisms are still under investigation. In regard to the therapeutic function of MLT, in vivo MLT application restored autophagic flux to impede cognitive decline and cardiac anomalies in Alzheimer’s disease (AD) animal models [ 27 , 28 ]. More recently, MLT was demonstrated to downregulate PI3K/AKT in stem cells through the MLT receptor (MT) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The property of MLT-mediated regulation of autophagy could also bene t in some age-related diseases. It was found that MLT in-vivo application ameliorated AD-induced cardiac atrophy [28], and enhanced the impeded cognitive function in tau-related AD rats [27] by restoring the autophagic ux. What's more, MLT could improve degradation of damaged mitochondria by mitophagy during aging and under neurodegenerative conditions [56].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it should be superior to other adjuvant in terms of safe, cost-effective and e cacy for large-scale of cellular materials undergone long-term expansion, despite the comprehensive mechanisms are still under investigation. When it comes to the therapeutic function of MLT, it is found that in-vivo MLT application could restore autophagic ux to impede cognitive decline and cardiac anomalies in Alzheimer disease (AD) animal models [27][28]. More recently, MLT demonstrated to down-regulate the PI3K/AKT in stem cells through MLT receptor (MT) [29].…”
mentioning
confidence: 99%
“… 192 (Table 2 ) For example, in Alzheimer’s disease (AD)-associated cardiac dysfunction, mutations of AD genes PS1 (presenilin 1), and PS2 suppressed mitophagy and contractile function through downregulating the cGAS/STING signaling. 193 …”
Section: Roles Of Cgas In Human Autoimmune and Inflammation Diseasesmentioning
confidence: 99%